Individual and combined associations of estimated pulse wave velocity and systemic inflammation response index with risk of stroke in middle-aged and older Chinese adults: a prospective cohort study - Xu, Man; Wang, Wenqiang; Chen, Ruoling; Zhou, Li; Hu, Hui; Qiao, Guiyuan; Wang, Ling; Liu, Xuezhen; Wang, Qiuhong; Ai, Yating; Ren, Hairong; Hu, Ping (Frontiers in Cardiovascular Medicine, 2023)
Background and aims Estimated pulse wave velocity (ePWV) and systemic inflammatory response index (SIRI) have been recently investigated as a marker of arterial stiffness and a novel systemic inflammatory indicator. This study aims to examine the independent and combined association of ePWV and SIRI with incident stroke and its subtypes. Methods Data of the Dongfeng-Tongji cohort study was analyzed for 9,154 middle-aged and older adults, who were free of cardiovascular disease and cancer and were followed up to document incident stroke. But their association with incident stroke events and its subtypes have not been well studied. Multivariable adjusted Cox regression models were used to determine the independent and combined association of ePWV and SIRI with incident stroke events. Results Over a 7.22-year follow-up, the cohort documented 491 stroke cases (387 ischemic stroke and 104 hemorrhagic stroke). The multivariate adjusted model showed that with each one-unit increase in the level of ePWV, the corresponding hazard ratios (HRs) (95% CI) for total stroke, ischemic stroke, and hemorrhagic stroke were 1.53 (95% CI, 1.23–1.90), 1.42 (95% CI, 1.11–1.83), and 1.92 (95% CI, 1.21–3.03), respectively. Similarly, with each one-unit increase in log-transformed levels of SIRI, the corresponding HRs (95% CI) for total stroke, ischemic stroke, and hemorrhagic stroke were 1.23 (95% CI,1.04–1.47), 1.16 (95% CI, 0.96–1.41), and 1.52 (95% CI, 1.05–2.20), respectively. There appeared to be a combined effect of ePWV and SIRI on stroke; Participants with high levels of both ePWV and SIRI had a higher risk of total stroke and hemorrhagic stroke, with multiple adjusted HR of 2.43 (95% CI, 1.09–5.42). Additionally, the incorporation of ePWV in addition to traditional cardiovascular risk factors significantly improved the predictive accuracy for total stroke with C statistic increased from 0.684 (95% CI, 0.661–0.707) to 0.687 (95% CI, 0.664–0.710; x2 = 6.65; p for difference = 0.010), and (suggestively) for ischemic stroke with C statistic increased from 0.684 (95% CI, 0.659–0.71) to 0.691(95% CI, 0.666–0.717; x2 = 3.13, p for difference = 0.077), respectively. Conclusions The presence of both high ePWV and SIRI individually, as well as together, was found to be associated with an increased incidence of stroke. The combined stroke risk assessment using these two indicators could potentially improve non-invasive assessment and treatment strategies for high-risk patients, as these indicators are easily accessible in clinical practice.